When Does Differential Item Functioning Matter for Screening? A Method for Empirical Evaluation. (March 2021) - Gonzalez, Oscar; Pelham, William E.
When items in a screening measure exhibit differential item functioning (DIF) across groups (e.g., males vs. females), DIF might affect which individuals are "caught" in the screening. This phenomenon is common, but DIF detection procedures do not typically provide guidance on whether the presence of DIF will meaningfully affect screening accuracy. Millsap and Kwok proposed a method to quantify the impact of DIF on screening accuracy, but their approach had limitations that prevent its use in scenarios where items are discrete. We extend the Millsap and Kwok procedure to accommodate discrete items and provide R functions to apply the procedure to the user's own data. We illustrate our approach using published screening information and evaluate the proposed methodology with a small simulation study. Overall, we encourage researchers to use empirical methods to evaluate the extent to which the presence of DIF in a screening measure materially affects screening performance.